KEBIJAKAN PERLUASAN ALAT BUKTI HUKUM ACARA PIDANADALAM UPAYA MEWUJUDKAN KEPASTIAN HUKUM BERKEADILAN - Ani Triwati; A. Heru Nuswanto; Endah Pujiastuti (Universitas Semarang, 2017)
One of the renewal of legal instruments in criminal procedural law is the expansion of evidence ie electronic information and / or electronic document and / or its printed outcome. Arrangement of evidence in criminal procedural law in Indonesia pursuant to Article 184 KUHAP, Article 5 paragraph (1) and (2) and Article 44 letter of Information and Electronic Transaction Act, covering witness statements, expert information, letters, instructions, defendants, electronic information and / or electronic documents and / or prints. The decision of the Constitutional Court Number 20 / PUU-XIV / 2016 that for electronic information and / or electronic document as evidence is done in the framework of law enforcement at the request of the police, prosecutor and / or other law enforcement institutions determined by law. Electronic information and / or electronic documents as evidence must be obtained in accordance with the provisions of Article 31 paragraph (3) of the Information and Electronic Transactions Act, this relates to the value of legal certainty and the value of justice for the litigant